Fever in Steven Johnson Syndrome , a case report - Qato, Migena; Kraja, Dhimiter; Como, Najada (International Journal of Scientific Research and Management (IJSRM), 2018)
Steven Johnson syndrome is a life threatening clinical condition that is  usually manifested with fever , rash, bullous formation, oral and ocular lesions and genital and anal lesions. This syndrome, in majority of cases  begins with influenza-like symptoms and continues with a red rash and blisters . Then the top layer of the affected skin dies and sheds.[1,2] This case report is about a 28 year old male patient who was referred to the Infectious Disease Hospital of University Hospital Center Mother Theresa Tirana with the suspected diagnosis of Hemorrhagic Fever. The patient referred 5 days of  continuous fever, malaise, rash, myalgia, headache, and nausea As soon as the patient was admitted, we immediately performed specific serologic tests, therapeutic regimen for the suspected diagnosis of  hemorrhagic fever and complementary examination. During the first 10 hours, we noticed that the rash became more intense and other skin lesion and bullous formation appeared. The patient was admitted in ICU and initial diagnosis of Steven Johnson Syndrome was made. This case report elaborates the particular clinical appearance and the misdiagnosis that was associated with Steven Johnson Syndrome.[3] Specific conditions as the prolonged prodromal phase of SJS, the strong epidemiological data for hemorrhagic fever, the absence of information for misuse of drugs led us towards a “sure diagnosis” in the first place. However, the close follow-up in the ICU revealed new clinical signs and rapid differential diagnosis was done. Due to the intensive care therapy, which was applied for Hemorrhagic fever at first place, we managed to overcome complications and safe the patient life.[4]